(untitled) (Journal of Asian Development Studies, 2024)
Climate change is exacerbating both water scarcity and water-related hazards as rising temperatures disrupt precipitation patterns and the entire water cycle. Water is crucial for all types of living creatures; therefore, its availability and quality are important for humans, too. However, water-related issues have increased all over the world, and people are facing more difficulties than in the past. Water scarcity is the most obvious issue, which results from the imbalance between water demand and supply. Ithas numerous negative effects on community health and societal development. This study was undertaken in the agriculturally oriented rural locale of district Rawalpindi in Pothwar, region of Punjab, Pakistan. The study primarily assessed the magnitude of water scarcity and, further investigated the impact of water scarcity on the health of the local community and looked into the problems faced by women and children. A sample size of one hundred respondents was selected using the probability technique of Simple Random Sampling. Both qualitative and quantitative techniques were used in collecting and analyzing data for this field research. The major sources of water in the locale are distant natural wells. The research indicated that local inhabitants faced many difficulties in tapping distant natural water resources to meet their daily needs. Water is generally stored in plastic drums and plastic tanks, but some local people have also constructed underground concrete tanks. The water used for drinking and meeting various others’ needs is contaminated, impure, unclean and hard. As a consequence, several diseases such as diarrhea, vomiting, kidney disorders and jaundice are common in the locale inhabitants because of water scarcity, which forces the people to use water from contaminated resources. Further, they have to bear expenses on the disease treatment, and spend extra money for fetching water